Pengaruh Program MBKM Kampus Mengajar terhadap Keterampilan Softskill Mahasiswa Universitas Negeri Gorontalo (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to determine the influence of the Independent Learning Independent Campus Program (MBKM) on the soft skills of students of the class of 2021 in the Department of Economic Education, Gorontalo State University. The method used is quantitative with an explanatory approach, which aims to explain the causal relationship between the variables of the MBKM program and students' soft skills. Primary data was obtained through the distribution of questionnaires to 35 respondents who were active students in the batch. Data analysis was performed using simple linear regression with the help of SPSS software version 21. The results of the study show that the MBKM Program has a positive and significant influence on students' soft skills. This means that the higher the level of student involvement in the MBKM program, the better their abilities in terms of communication, teamwork, time management, adaptability, and confidence. The magnitude of the influence of the MBKM program on students' soft skills reached 65.3%, while the remaining 34.7% was influenced by other factors that were not discussed in this study. These findings provide important implications for the development of curriculum and learning strategies in higher education, especially in integrating the MBKM program as an effort to improve the quality of graduates who are ready to face the challenges of the world of work and global society.